2021
DOI: 10.1016/j.envint.2021.106790
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms underlying the health effects of desert sand dust

Abstract: Highlights 52 studies investigating mechanisms behind impacts of desert dust on health are reviewed. Desert dust may be a risk factor for inflammatory and allergic lung diseases. Adhered chemicals, biological and mineralogical components are candidate activators. Desert dust surface reactions may enhance toxicity of aerosols in urban environments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(26 citation statements)
references
References 111 publications
(170 reference statements)
0
21
0
Order By: Relevance
“…It has been considered that these organic and inorganic pollutants were simultaneously long-range transported to Japan by westerly winds. They are thought to be common causes of hospital admission for respiratory, cerebrovascular, and cardiovascular diseases [10], cough prevalence [11][12][13], itchy eyes [14], asthma exacerbation [15], and seasonal allergic rhinitis [7,16].…”
Section: Introductionmentioning
confidence: 99%
“…It has been considered that these organic and inorganic pollutants were simultaneously long-range transported to Japan by westerly winds. They are thought to be common causes of hospital admission for respiratory, cerebrovascular, and cardiovascular diseases [10], cough prevalence [11][12][13], itchy eyes [14], asthma exacerbation [15], and seasonal allergic rhinitis [7,16].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the composition of dust aerosols may change during long-distance transportation, particularly atmospheric bacterial levels and community diversity would signi cantly increase. These dust aerosols may increase the level of pro-in ammatory mediators and airway in ammation by activating the TLR2 and NALP3 in ammatory pathways in alveolar macrophages [44] , which may nally increase the risk of in uenza. Another explanation could also be the great sensitivity of in uenza viral to climate [45,46] , and dust emissions may in uence the activity and transmission of viral.…”
Section: Discussionmentioning
confidence: 99%
“…Drought was associated with lower odds of completing childhood BCG, DPT, and polio vaccines, suggesting risk of future disease outbreaks 86 . In a systematic review, during droughts in India, the work burden on women and children increased, along with malnutrition and anemia 87 . Meanwhile, a review of experimental studies found a likely harmful effect of desert dust on asthma and respiratory infections, suggesting dust may be a platform for other chemicals that enhance its pulmonary toxicity 88 .…”
Section: Extreme Cold: "Everything Gets Worse If You Don't Have Elect...mentioning
confidence: 99%